Quantum Key Distribution in OpenSSL - Papotti, Aurora (My University, 2021)
Most of the current communications and systems rely on asymmetric cryptography, which is used to share a unique secret key between two parties communicating, in order to encrypt the information exchanged. Recently, many researchers state that quantum computing will be a threat in 15-20 years. At the moment there is no quantum computer able to crack classical cryptography, however, a solution to address the threat should be found as soon as possible before classical cryptography reaches its expiration date, and all communications and systems will be cracked. Quantum cryptography is considered a problem, but from another perspective, it is also the solution to it. In fact, this technology is strong enough to protect both from quantum and classical attacks. Quantum cryptography is considered secure because it is based on quantum physics laws. The benefits of quantum cryptography, combined with the ones of symmetric cryptography offer an alternative solution to the Key Exchange problem: Quantum Key Distribution (QKD). The technology is a protocol that describes a cryptographic technique to exchange a secret key between two end users/applications within a communication. This thesis starts by presenting the quantum threat, and the reasons that make quantum computing risky for classical communications and systems. Moreover, it states the importance to invest resources in this field of research in order to find a solution to address the problem once it will be a real risk. Finally, I explain my contribution to Cefriel activities in the context of Quantum Key Distribution. The internship activity described is a demonstrative approach to integrate QKD technology into the OpenSSL library. The project aims to demonstrate the effectiveness and the feasibility of using QKD technology in SSL communications.
Keywords: Asymmetric Cryptography, Symmetric Cryptography, Quantum Cryptography, Quantum Key Distribution, TLS/SSL, OpenSSL